Exposing Mississippi : Eudora Welty's photographic reflections - Trefzer, Annette, 1960- (Critical perspectives on Eudora Welty., 2022)
"Internationally known as a writer, Eudora Welty has as well been spotlighted as a talented photographer. The prevalent idea remains that Welty simply took snapshots before she found her true calling as a renowned fiction writer. But who was Welty as a photographer? What did she see? How and why did she photograph? And what did Welty know about modern photography? In Exposing Mississippi: Eudora Welty's Photographic Reflections, Annette Trefzer elucidates Welty's photographic vision and answers these questions by exploring her photographic archive and writings on photography. The photographs Welty took in the 1930s and '40s frame her visual response to the cultural landscapes of the segregated South during the Depression. The photobook One Time, One Place, which was selected, curated, and shaped into a visual narrative by Welty herself, serves as a starting point and guide for the following chapters on her spatial hermeneutic. The book is divided into sections by locations and offers how the framing of these areas reveals Welty's radical commentary of the spaces her camera captured. There are over eighty images in Exposing Mississippi, including some never-before-seen archival photographs, and sections of the book draw on over three hundred more. The chapters on institutional, leisure, and memorial landscapes address how Welty's photographs contribute to, reflect on, and intervene in customary visual constructions of the Depression South"--